Sugar : major trade and stabilization issues in the eighties (FAO RomeIT, 1985)
Discusses possible modifications in provisions and procedures that might improve the effectiveness of an international sugar agreement. Reviews trends in production, consumption, trade and prices of sugar, since 1960 looking also at post-war international sugar agreements. Presents perspectives on demand, supply and trade patterns in 1990. Proposes measures which might help to restore equilibrium in the world sugar economy.
DC